EFFECT OFSOAKING OF LIQUID SMOKE ON THE QUALITY OF CATFISH(Pangasius hypophthalmus)MEATBALLS DURING STORAGE IN COLD TEMPERATURE(5±2˚C) - Angraini, Yannisa; Sari, N. Ira; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was aimed to determine the effect of soaking the catfish (Pangasius hypophthalmus) meatballs into the liquid smoke on their quality of during storage in cold temperature (5±2˚C), to get the optimum concentration of the liquid smoke and to determine the shelf-life of catfish meatballs. The method used was an experimental method and composed as the Randomized Block Design (RBD). The fish meatballs were soaked ini varied concentrations of liquid smoke (0, 0.5, 1.0, 1.5, and 2.0 %) and then the products were stored and observed periodically for 5, 10, and 15 days. The parameter observed were the total number of bacteria plate count (TPC), Escherichia coli bacteria, Staphylococcus aureus bacteria, pH value and sensory evaluation (appearance, odor, taste and texture). The results showed that the use of 2% liquid smoke concentration was indicated the best treatment, as seen from lowest (total number bacteria plate count 4.5 x 104 Cfu/g, Coliformbacteria 3.00 MPN/g, negative in Escherichia colibacteria, Staphylococcus aureus 7.3x 101 Cfu/g), pH value 6.8during storage in cold temperature (5±2˚c),and the highest score of appearance 5.5 (little hole,brightless and includes in middle category) odor 5.6 ( quiickly rancid odor), taste 5.7 (quickly to acid) and texture 5.0(had incompact texture) could be stored for 10 days in cold temperatures(5±2oC).Keywords: catfish ,liquid smoke, quality, storage,